Is AI Approved by the FDA for Medical Diagnosis? A Regulatory Deep Dive - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2023)
Is AI Approved by the FDA for Medical Diagnosis? A Regulatory Deep Dive The integration of Artificial Intelligence (AI) and Machine Learning (ML) into h...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Machine Learning